Studi Kasus Pertumbuhan Dan Produksi Jagung Manis (Zea Mays Saccharata Sturt) Dan Tomat (Solanum Lycopersicum L.) Pada Sistem Tumpangsari Di Desa Dahana Tabaloho - Charles Septiawan Zebua; Marta Tristanti Mendrofa; Reza Septa Harita; Wendi Warisman Harefa; Yoel Melsaro Larosa (CV. SINAR HOWUHOWU, 2026)
This study aimed to describe the application of an intercropping system between sweet corn (Zea mays var. saccharata Sturt) and tomato (Solanum lycopersicum L.) practiced by farmers in Dahana Tabaloho Village. The research employed a descriptive case study approach. Data were collected through field observations, farmer interviews, and documentation of cultivation activities. The observed aspects included planting patterns, planting spacing, crop maintenance, fertilization, pest and disease management, and crop yields obtained by farmers. The results indicated that the intercropping system provided more efficient land utilization compared to monoculture systems by allowing two commodities to be cultivated simultaneously on the same land area. Furthermore, the system has the potential to improve land-use efficiency, diversify crop production, and increase farmers' income. However, challenges were identified, particularly competition among plants for light, water, and nutrients when planting arrangements were not properly managed. Therefore, the intercropping system of sweet corn and tomato in Dahana Tabaloho Village can serve as an effective land management alternative to enhance agricultural productivity and farming sustainability.